Conceptualizing Gender Inequality: An Intersectional Inquiry into Understanding CSOs’ Conceptualization of Gender Inequality - Nartey,Lina (2025)
The way in which gender inequality (GI) is conceptualized contributes to determining approaches to overcome it and, ultimately, to achieve gender equality. There has been little previous research on the conceptualization of GI by civil society organizations (CSOs). This thesis aims to improve our understanding of how CSOs conceptualize GI today, how they understand changes in how GI has been conceptualized over time, and what impact the changes have had on their daily work. The thesis does so by a qualitative interview study involving program officers from four Swedish CSOs engaged in working towards gender equality. The results show that there is a variation between the CSOs’ conceptualizations and that the conceptualizations have changed over time. The results also show that an emerging anti-gender agenda in the broader political landscape has impacted the work of CSOs negatively. This thesis discusses several policy implications of the results.
Keywords: Gender inequality; Civil Society Organizations; Development Cooperation; Conceptualizations; Conceptual Change; Intersectionality; Gender Equality